Specialist accommodation operations in North Queensland: barriers to the implementation of environmental management practices. (7th May 2009) - Carmody, Julie; Zeppel, Heather
There are situational variables affecting the implementation of environmental management practices by specialist (or boutique) accommodation operators located near protected areas in Far North Queensland. These styles of accommodation are small, owner-operated establishments offering special activities, features or services to the guest and have a high host?guest interaction. From a survey sample of 101 specialist accommodation operations, 30 owners were personally interviewed at their establishment to better understand key factors affecting the implementation of environmental management practices for water, energy, waste and other sustainable practices. Environmental management techniques that are both simple and cost-effective are easily implemented by specialist accommodation operators. However, situational factors such as cost, lack of knowledge, climatic conditions, available municipal infrastructure and legislation appear to impede the uptake of some sustainable management practices.